RND3 Potentiates Proinflammatory Activation through NOTCH Signaling in Activated Macrophages - María José Romero de Ávila; Susana López-López; Aarón García-Blázquez; Almudena Ruiz-García; María Julia González-Gómez; María Luisa Nueda; Victoriano Baladrón; Ignacio Pérez-Roger; Enric Poch; Begoña Ballester-Lurbe; José Javier García-Ramírez; Eva M. Monsalve; et al. (Journal of Immunology Research)
Macrophage activation is a complex process with multiple control elements that ensures an adequate response to the aggressor pathogens and, on the other hand, avoids an excess of inflammatory activity that could cause tissue damage. In this study, we have identified RND3, a small GTP-binding protein, as a new element in the complex signaling process that leads to macrophage activation. We show that RND3 expression is transiently induced in macrophages activated through Toll receptors and potentiated by IFN-γ. We also demonstrate that RND3 increases NOTCH signaling in macrophages by favoring NOTCH1 expression and its nuclear activity; however, Rnd3 expression seems to be inhibited by NOTCH signaling, setting up a negative regulatory feedback loop. Moreover, increased RND3 protein levels seem to potentiate NFκB and STAT1 transcriptional activity resulting in increased expression of proinflammatory genes, such as Tnf-α, Irf-1, or Cxcl-10. Altogether, our results indicate that RND3 seems to be a new regulatory element which could control the activation of macrophages, able to fine tune the inflammatory response through NOTCH.